2019
DOI: 10.1371/journal.pone.0211708
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of cytopenias among antiretroviral therapy naïve Human Immunodeficiency Virus infected adults in Dessie, Northeast Ethiopia

Abstract: Background Hematologic abnormalities involving peripheral blood cell cytopenias are strong predictors of morbidity, mortality and poor antiretroviral therapy (ART) outcomes of HIV infected individuals. However, limited studies are conducted in resource-limited settings of sub-Saharan Africa that have addressed the magnitude and associated factors of cytopenias. This study aimed to investigate the magnitude and associated factors of cytopenias among ART naïve HIV infected adult Ethiopians. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 37 publications
6
25
1
Order By: Relevance
“…As other authors already observed [23], a comprehensive haematologic analyses showed the high prevalence of one or more cytopenia of any type (40,1%) in patients with severe HIV disease. In our opinion, however, this is only one aspect of the problem.…”
Section: Plos Onesupporting
confidence: 77%
“…As other authors already observed [23], a comprehensive haematologic analyses showed the high prevalence of one or more cytopenia of any type (40,1%) in patients with severe HIV disease. In our opinion, however, this is only one aspect of the problem.…”
Section: Plos Onesupporting
confidence: 77%
“…As anemia, there is no generally accepted cut-offs for leucopenia and thrombocytopenia; we defined them as used in other studies [19,27]. Leucopenia was defined as a total WBC < 4.0 × 103/μL, whereas thrombocytopenia was defined as a total platelet count < 150 × 103/μL.…”
Section: Plos Onementioning
confidence: 99%
“…5,7,11 Previous studies conducted in Ethiopia reported the magnitude of anemia among adult HIV patients on ART ranges from 23-43.5%. 13,20 Being female, illiterate, or ART naïve; having a history of taking anti-TB treatment; taking a Zidovudine (ZDV)-containing ART regimen; CD4+ T-lymphocyte count; nutritional status; body mass index (BMI); and WHO clinical stage of HIV/AIDS are important factors associated with the occurrence of anemia among adults HIV patients on ART. 13,18 Despite the widely divergent socioeconomic factors that characterize HIV worldwide, the degree of clinical anemia remains an independent risk factor for predicting mortality from HIV, even upon initiation of therapy.…”
Section: Introductionmentioning
confidence: 99%